Early termination compensation under demand uncertainty in public-private partnership projects - Song, Jinbo; Yu, Yanzhu; Jin, Lulu; Feng, Zhuo (International Journal of Strategic Property Management, 2018)
In the early termination of public-private partnership (PPP) projects, compensation is considered a core issue that greatly affects the interests of the government and the private sector. To address the early termination that is frequently caused by government default or voluntary buyback, this paper proposes an ex-ante compensation mechanism using the cumulative probability that a given demand could be realized to determine early termination compensation under demand uncertainty. By splitting the compensation into two parts, the base compensation could be the minimum compensation for the private sector, while the additional compensation is considered a reasonable allocation of future booming demand. The predetermined compensation criterion ensures a smooth transfer of the early terminated project, which not only benefits the government from being overcharged, but also enables the private sector to gain a reasonable compensation for the remaining concession period.